1999
DOI: 10.1364/ao.38.001434
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of NO A–X(0, 2) laser-induced fluorescence: investigation of calibration and collisional influences in high-pressure flames

Abstract: Laser-induced-fluorescence techniques have been used successfully for quantitative two-dimensional measurements of nitric oxide. NO A-X(0, 2) excitation at 248 nm recently found applications in internal-combustion engines. We assess the collisional processes that influence quantification of signal intensities in terms of saturation, rotational energy transfer, and line broadening, using laminar high-pressure methane/air and n-heptane/air flames at pressures as high as 80 bars (8 x 10(6) Pa). A calibration meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…not notably altered by the addition of NO up to a quantity of 2000 ppm. These results are in agreement with the literature: Schulz et al [7] reported that a 10% reduction is observed when 1500 ppm NO is added in the combustion chamber of a methane-fueled optical-engine operating in lean conditions (f ¼ 0:9). Further, it is important to note that the chemical NO/O 2 instability (that forms NO 2 and removes NO molecules via the oxidation reaction NO+NO+O 2 -2 NO 2 ) does not change considerably the quantity previewed to be inside the combustion chamber, because of the low residence time of the entering load in the intake port (85 ms) [40].…”
Section: Fired Engine Experiments With No Additionsupporting
confidence: 93%
See 1 more Smart Citation
“…not notably altered by the addition of NO up to a quantity of 2000 ppm. These results are in agreement with the literature: Schulz et al [7] reported that a 10% reduction is observed when 1500 ppm NO is added in the combustion chamber of a methane-fueled optical-engine operating in lean conditions (f ¼ 0:9). Further, it is important to note that the chemical NO/O 2 instability (that forms NO 2 and removes NO molecules via the oxidation reaction NO+NO+O 2 -2 NO 2 ) does not change considerably the quantity previewed to be inside the combustion chamber, because of the low residence time of the entering load in the intake port (85 ms) [40].…”
Section: Fired Engine Experiments With No Additionsupporting
confidence: 93%
“…Adding NO to the burning mixture may help us to determinate the lower level of detectable absorption from this molecule under the combustion chamber conditions. Unfortunately, previous works [7,[36][37][38] showed that nitric oxide seeding might change the flame characteristics. Its interaction with the combustion process leads to a reduction in the nitric oxide concentration as a consequence of NO reburn reaction [39].…”
Section: Fired Engine Experiments With No Additionmentioning
confidence: 97%
“…The variation of NO-LIF signal intensity with temperature, however, leads to an increase of approximately 20% per 200 K above 2000 K. The variation of NO-LIF signal intensities found at different operation conditions and different detection timings is much larger and therefore significant even without detailed knowledge about local temperatures. Calibration of signal intensities by doping NO to the fresh gases used in homogeneous gasoline engine combustion [11] is not feasible here since local variations in fuel concentration lead to unpredictable levels of NO reburn. On the other hand, adding NO to the motored engine provides only insufficient signal intensities due to negligible population of the probed vibrational level.…”
Section: Resultsmentioning
confidence: 99%
“…While in situ calibration has been performed in engines under homogeneous lean conditions by adding NO to the feedstock gases [4,8,25] where $90% of the NO survives the flame chemistry [26], technical restrictions due to the realistic engine setup prohibited this method in our experiments. Instead, we use a miniature calibration burner (20 cm long, 8-mm-diameter metal tube) that was inserted into the cylinder through the spark plug hole.…”
Section: Calibrationmentioning
confidence: 99%